ECOLOGICAL AWARENESS IN THE 21ST CENTURY HINDI STORIES - A.K Bindhu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
20% of the population of developed countries consumes 80% of the earth’s resources and 80% of the rest of the world lives on 20% of the resources. The more resources are consumed, the more pollution will spread. To produce industrial products, man has started exploiting nature and creating a new culture by separating from it. Environmental destruction is its dangerous consequence. When the exploitation of nature started questioning the existence of humans, its response started reflecting through literature. The capitalist mentality that takes away the right to live by unfairly exploiting nature is visible in the literature of the twenty-first century. A culture moving towards development versus destruction shows the decline of the entire human race. The stories of the twenty-first century draw our attention to this horrific reality. Mangosil is proof of this.